COVID-19 an oportunnity or a disaster for undergraduate medical education? - Flores Quiroga, Rodrigo Fernando (2021)
This letter expresses a novel opinion on the prospects for undergraduate medical education during the COVID-19 pandemic. It reviews traditional medical education and the benefits and harms of new educational models, such as telemedicine.